Concise Synthesis of the Repeating Units of the Cell Wall Lipopolysaccharide of Azospirillum brasilense SR80 - Mandal, Pintu Kumar; Dhara, Debashis; Misra, Anup Kumar (Synthesis, 2014)
Syntheses of trisaccharide and tetrasaccharide repeating units of the cell wall lipopolysaccharide of Azospirillum brasilense SR80 as their 4-methoxyphenyl (PMP) glycosides have been achieved following a sequential glycosylation strategy in good yield. All intermediate steps are high-yielding and the glycosylation steps are highly stereoselective.
Keywords: Azospirillum brasilense; tetrasaccharide; trisaccharide; lipopolysaccharide; plant-growth-promoting bacteria